Alterations of brain activity in multiple system atrophy patients with freezing of gait: A resting-state fMRI study - Cheng, Yilin; Yang, Huaguang; Liu, Weiyin Vivian; Wen, Zhi; Chen, Jun (Frontiers in Neuroscience, 2022)
Backgrounds: Freezing of gait (FOG) in multiple system atrophy (MSA) is characterized by a higher risk of falls and a reduced quality of life; however, the mechanisms underlying these effects have yet to be identified by neuroimaging. The aim of the present study was to investigate differences in gray structure and function when compared between MSA patients with and without freezing. Methods: Degree centrality (DC) based on resting-state functional magnetic resonance imaging was computed in 65 MSA patients and 36 healthy controls. Brain regions with statistically different DC values between groups were selected as seed points for a second seed-based functional connectivity (FC) analysis. The relationships between brain activity (DC and FC alterations) and the severity of freezing symptoms were then investigated in the two groups of MSA patients. Results: Compared to MSA patients without FOG symptoms (MSA-nFOG), MSA-FOG patients showed an increased DC in the left middle temporal gyrus but a reduced DC in the right superior pole temporal gyrus, left anterior cingulum cortex, left thalamus and right middle frontal gyrus. Furthermore, in MSA-FOG patients, the DC in the left thalamus was negatively correlated with FOG scores. Using the left thalamus as a seed, secondary seed-based functional connectivity analysis revealed that MSA-FOG patients commonly showed left thalamus-based FC abnormalities in regions related to cognition and emotion. In contrast to the MSA-nFOG patients, MSA-FOG patients showed an increased FC between the left thalamus and the left middle temporal gyrus (MTG), right inferior parietal lobule (IPL), bilateral cerebellum_8 and left precuneus. Conclusion: FOG is associated with centrality of the impaired thalamus network. Abnormal FC between the thalamus and left MTG, right IPL, bilateral cerebellum_8 and left precuneus was involved in FOG. These results provide new insight into the pathophysiological mechanism of FOG in MSA. Key words: Multiple system atrophy; Freezing of gait; Degree centrality; Functional connectivity.